121k views
2 votes
Consider the Equation
x^2-10x-11=0

User Fostah
by
5.6k points

2 Answers

1 vote

Answer: x^{2} - 10x - 11 = 0

x^{2} - 10x = 11

x = -1

; -1^{2} - 10(-1) = 11

1 + 10 = 11

User Bernette
by
5.2k points
4 votes

Answer:

x = - 1, x = 11

Explanation:

Given

x² - 10x - 11 = 0

Consider the factors of the constant term (- 11) which sum to give the coefficient of the x- term (- 10)

The factors are - 11 and + 1, since

- 11 × 1 = - 11 and - 11 + 1 = - 10, thus

(x - 11)(x + 1) = 0

Equate each factor to zero and solve for x

x - 1 = 0 ⇒ x = 11

x + 1 = 0 ⇒ x = - 1

User Hyemi
by
5.1k points